1994
DOI: 10.1107/s0907444994005263
|View full text |Cite
|
Sign up to set email alerts
|

Refined crystal structure of liver alcohol dehydrogenase–NADH complex at 1.8 Å resolution

Abstract: The crystal structure of the ternary complex of horse liver alcohol dehydrogenase (LADH) with the coenzyme NADH and inhibitor dimethyl sulfoxide (DMSO) has been refined by simulated annealing with molecular dynamics and restrained positional refinement using the program X-PLOR. The two subunits of the enzyme were refined independently. The space group was P1 with cell dimensions a = 51.8, b = 44.5, c = 94.6 A, alpha = 104.8, beta = 102.3 and gamma = 70.6 degrees. The resulting crystallographic R factor is 17.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
100
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(108 citation statements)
references
References 2 publications
7
100
0
1
Order By: Relevance
“…The average zinc-ligand distances in the molecular dynamics simulations of alcohol dehydrogenase are in excellent agreement with the crystal structure of the enzyme 4 Table VII show that DMSO binds more strongly to the zinc ion than water; the Zn-O distance is 2.12 Å for DMSO compared to 2.26 Å for H 2 O with similar basis sets (Table III).…”
Section: Zinc-ligand Distancessupporting
confidence: 64%
See 2 more Smart Citations
“…The average zinc-ligand distances in the molecular dynamics simulations of alcohol dehydrogenase are in excellent agreement with the crystal structure of the enzyme 4 Table VII show that DMSO binds more strongly to the zinc ion than water; the Zn-O distance is 2.12 Å for DMSO compared to 2.26 Å for H 2 O with similar basis sets (Table III).…”
Section: Zinc-ligand Distancessupporting
confidence: 64%
“…Throughout, the coordinates of horse liver alcohol dehydrogenase in complex with NADH and dimethylsulfoxide at 1.8 Å resolution (R-factor=0.172) 4 were used. This is at present the most accurate structure of alcohol dehydrogenase.…”
Section: The Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystallographic studies of the horse liver enzyme (Eklund et al, 1981, Eklund & Brändén, 1983, Al-Karadaghi et al, 1994 have shown that the latter zinc ion is bound to the enzyme by four cysteine residues. As can be seen in Table 1, the coordination geometry around this zinc ion is almost tetrahedral, with small but reproducible differences between the ligands.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme has been thoroughly studied and the crystal structure is known for several complexes (Eklund et al, 1981, Eklund & Brändén, 1983, Al-Karadaghi et al, 1994. Furthermore, if all the cysteines are deprotonated, there are eight equivalent Zn-S bonds in the enzyme, which gives a very accurate estimate of the average Zn-S bond length.…”
Section: Introductionmentioning
confidence: 99%